Secular/Religious Myths of Violence: The Case of Nizārī Ismailis of the Alamūt Period - Mohammad Poor, Daryoush (Studia Islamica, 2020)
Contemporary narratives of violence, particularly in the aftermaths of the most recent expressions of violence by the so-called Islamist' groups have rekindled the false dichotomy of religious versus secular violence. Such a deforming prism which has also become dominant in political science traces the origins of violence to faith communities in medieval times and, among others, to Nizārī Ismailis, with whom the myth of the assassins have been associated. Despite the ground-breaking works of prominent scholars of Ismaili studies, the myth of the assassins still remains powerful in some disciplines including political theory. This paper deconstructs this narrative and attempts to highlight the agencies of individuals and communities, as human agents, as opposed to essentialist narratives in which faith, or a particular faith, in its abstraction, becomes responsible for the outbreak of violence. Moving beyond reductionist narratives of violence is critical for breaking the vicious cycle of violence which besets human societies around the globe.